(untitled) (International journal of artificial intelligence, 2024)
The creation of an electronic library coupled with the ability to identify similar texts plays a crucial role in the management and validation of content in various fields such as academia, publishing, and legal sectors. This paper discusses the functional structure of a system designed to store, organize, and retrieve documents while leveraging text comparison algorithms to detect similarities or potential plagiarism. The system integrates components such as a Library Management System (LMS), text processing and indexing modules, a similarity detection engine, and an intuitive user interface. By utilizing advanced text comparison algorithms like cosine similarity, Jaccard index, and machine learning models, the system enables efficient text similarity detection, thereby improving content validation and ensuring document integrity. The functional structure also emphasizes scalability, user experience, and the seamless integration of document storage, indexing, and comparison tasks.